IgA Nephropathy in a Patient Presenting with Pseudotumor Cerebri - Umair Syed Ahmed; Patrick Bacaj; Hafiz Imran Iqbal; Songul Onder (Case Reports in Nephrology, 2016)
IgA nephropathy is the most common glomerulonephritis worldwide and typically has minimal signs for chronicity in histopathology at the time of initial presentation. Pseudotumor cerebri (PTC) is characterized by increased intracranial pressure in the absence of any intracranial lesions, inflammation, or obstruction. PTC has been reported in renal transplant and dialysis patients, but we are unaware of any reports of pseudotumor cerebri in patients with IgA nephropathy. We report a case of a young female who presented with signs and symptoms of pseudotumor cerebri and was subsequently diagnosed with IgA nephropathy and end-stage renal disease. To our knowledge this is the first report of IgA nephropathy presenting as end-stage renal disease in a patient who presented with pseudotumor cerebri.